Optimization of Pectic-Oligosaccharide Production from Banana Peel Pectin Using Ultrasound Technique for Green Depolymerization - Hidayati, Nisa Arum; Hasanah, Uswatun; Suyatma, Nugraha Edhi (Indonesian Food Science and Technology Journal, 2026)
Banana peels, which are considered agricultural waste, contain up to 22.4% pectin. The extracted pectin can be treated by the ultrasound technique as a green synthesis method to produce pectic-oligosaccharides (POS). The combination of ultrasound time and amplitude is crucial for POS production. Therefore, this study aims to optimize the production of banana peel POS using ultrasonication as green depolymerization and to investigate its prebiotic potency. Optimization using a Central Composite Design (CCD) model by varying time (10-30 min) and amplitude (20-60%) with viscosity (cP) and molecular weight (g/mol) as main responses. This study found that the optimal ultrasound treatment was the combination of 25.085 min and 60% amplitude, resulting in banana peel POS with a viscosity of 55 cP and molecular weight of 28045.92 g/mol. Furthermore, the optimal POS scored a prebiotic activity of 1.22, indicating that banana peel POS can act as a prebiotic alternative. The addition of POS was more favorable for the selective metabolism of the probiotic L. paracasei Lpc-37 compared to enteric E. coli ATCC 25922. FTIR spectra confirmed that the ultrasound treatment broke the hydrogen bonds, resulting in POS with shorter chains. In addition, simple sugar chains were still observed in the fingerprint area. The results showed that ultrasound altered the pectin chain without changing the unique pattern, thereby improving its prebiotic activity. The POS obtained as a potential prebiotic retains its viscosity properties, pointing to its potential for use in various applications.